Le foncier en Méditerranée : une dichotomie entre Nord et Sud ? - Mélanie Requier-Desjardins; Romain Melot; Jean-Christophe Paoli; Orlando Rodrigues; Jeanne Riaux (Développement Durable et Territoires)
This introduction brings together the arguments from the texts of the special section « Transformations of Rural Land and Collective Strategies in the Mediterranean : Between Conflicts and Territorial Resilience », and from the literature, with the aim of showing that Mediterranean land tenure and property-rights topics shares similar entries on both sides of the Mediterranean. This concerns the observations and analyses made on land dynamics together with the methodological and conceptual approaches used in the North and South of the Mediterranean.